Electronic note taking technology and academic performance in nursing students. Issue 3 (4th July 2021) - Emory, Jan; Teal, Tabatha; Holloway, Ginger
Abstract : Background : Technological advances have provided alternatives to traditional handwritten note taking that are changing the classroom learning environment in higher education for nursing students. Aims : The purpose of this study was to explore nursing student attitudes and preferences for note taking and the relationship of note taking methods on academic performance. Design: The mixed method approaches collected data from 217 nursing students in a baccalaureate program of study in spring and fall of 2017. Methods : Nursing students at the junior and senior level in the academic program voluntarily participated by completing a survey using a Likert-type scale and open-ended questions. Findings : The majority of students (69.3%) reported taking notes by electronic methods. No significant difference was found between the method of note taking and GPA ( p = .139). Conclusions : Findings suggest that multiple variables influence learning in the classroom environment and note taking method has little impact on academic performance. Impact Statement: Educators should consider this finding when implementing policies on classroom electronics, including note taking. Understanding that the preferred method of note taking whether handwritten or electronic has little impact on overall academic performance should inform evidence based teaching and learning.